2020
DOI: 10.1007/s10567-020-00311-7
|View full text |Cite
|
Sign up to set email alerts
|

A Cognitive Model of Pathological Worry in Children and Adolescents: A Systematic Review

Abstract: Worry is common in children and adolescents, yet some youth experience excessive worries that persist over time and cause significant distress. Whilst the literature on worry and generalised anxiety disorder (GAD) in adults is well established, relatively less is known about the cognitive mechanisms underlying child and adolescent worry. An influential cognitive model of adult pathological worry (Hirsch and Matthews in Behav Res Therapy 50:636-646,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 81 publications
3
32
0
3
Order By: Relevance
“…In terms of health risk behaviours, high sedentary behaviour, having experienced multiple serious injuries, current tobacco use and ever cannabis use increased the likelihood of having WISD. These findings concur with previous studies [ 8 , 14 , 18 , 19 ]. In a systematic review, Yang et al [ 27 ] showed that prolonged sedentary behaviour was associated with sleep disturbance.…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…In terms of health risk behaviours, high sedentary behaviour, having experienced multiple serious injuries, current tobacco use and ever cannabis use increased the likelihood of having WISD. These findings concur with previous studies [ 8 , 14 , 18 , 19 ]. In a systematic review, Yang et al [ 27 ] showed that prolonged sedentary behaviour was associated with sleep disturbance.…”
Section: Discussionsupporting
confidence: 94%
“…The investigation aimed to estimate the prevalence and correlates of WISD in school adolescents in Lebanon. The prevalence of past 12-month WISD (14.7%) in this study, which was higher than in the 2011 Lebanon GSHS (10.3%) and globally (7.8%), but was lower than in other countries in the Middle East region, e.g., Kuwait (18.9%) and Qatar (17.9%) [ 8 ]. Previous studies among adolescents in the Lebanon confirm the high prevalence of sleep disturbance and anxiety disorders [ 9 , 10 ], calling for school sleep and mental health programmes in this adolescent population in Lebanon.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations